Study the Nuclear Structure of 42Ca and 42Ti Mirror Nuclei by Applying the Nuclear Shell Model Using Modified Surface Delta Interaction - Ali K. Hasan (Genius Journals, 2023)
The nuclear shell model was applied using the modified surface delta interaction MSDI tostudy the nuclear structure of the mirror nuclei
Keywords: Nuclear shell model, Excitation energies; Reduced transition probability of electric quadrupole B(E2), Modified surface delta interaction MSDI